Asuhan Kebidanan Komprehensif pada Ny. K Umur 30 Tahun G1P0A0 di Kelurahan Kampung Enam, Tarakan - Umi Suci Purnama Sari; Ari Widyaningsih (Universitas Ngudi Waluyo, 2025)
Continuity of Care (CoC) is a midwifery care approach that provides comprehensive and continuous services to women throughout pregnancy, childbirth, postpartum, newborn care, and family planning. This case study aims to describe the implementation of CoC midwifery care for Mrs. K, 30 years old, in Kampung Empat Village, Tarakan City, who experienced a physiological pregnancy during the first and second trimesters, but in the third trimester was diagnosed with umbilical cord entanglement and meconium-stained amniotic fluid, leading to a Sectio Caesarea (SC) procedure. The study employed a case study method using the seven-step Varney management approach and SOAP documentation. Data were collected through interviews, physical examinations, observations, and document reviews. The results showed that during the first trimester, the mother experienced mild nausea and vomiting that were managed through nutritional education and adequate rest. The second trimester progressed normally, while in the third trimester, signs of fetal distress were identified—specifically, a single umbilical cord loop around the fetal neck and meconium-stained amniotic fluid—prompting an SC procedure to prevent fetal asphyxia. A live male infant was born weighing 2,900 grams, measuring 49 cm in length, with an APGAR score of 8–9. The postpartum period was normal, the surgical wound healed well, breastfeeding was successful, and the mother chose the Copper T-380A IUD as a long-term contraceptive method. The implementation of CoC for Mrs. K highlights the importance of continuous monitoring to enable early detection of complications, enhance maternal readiness, and support the success of postpartum family planning programs. Abstrak Asuhan kebidanan berkesinambungan atau Continuity of Care (CoC) merupakan pendekatan pelayanan kebidanan yang diberikan secara menyeluruh dan berkesinambungan kepada ibu mulai dari masa kehamilan, persalinan, nifas, bayi baru lahir hingga keluarga berencana. Tujuan studi kasus ini adalah menggambarkan pelaksanaan asuhan kebidanan CoC pada Ny. K, usia 30 tahun, di Kelurahan Kampung Empat, Kota Tarakan, yang mengalami kehamilan fisiologis pada trimester I dan II, namun trimester III ditemukan lilitan tali pusat dan ketuban keruh sehingga dilakukan tindakan Sectio Caesarea (SC). Metode yang digunakan adalah studi kasus dengan pendekatan manajemen kebidanan tujuh langkah Varney dan pendokumentasian SOAP. Data diperoleh melalui wawancara, pemeriksaan fisik, observasi. dan studi dokumentasi. Hasil menunjukkan pada trimester I ibu mengalami mual muntah ringan yang dapat diatasi melalui edukasi gizi dan istirahat. Trimester II berjalan normal, sedangkan trimester III terjadi tanda gawat janin berupa lilitan tali pusat satu kali di leher janin dengan ketuban keruh, sehingga dilakukan SC untuk mencegah asfiksia. Bayi lahir hidup, laki-laki, berat badan 2.900 gram, panjang badan 49 cm, dan nilai APGAR 8–9. Masa nifas berlangsung normal, luka operasi sembuh baik, ASI eksklusif berjalan lancar, dan ibu memilih kontrasepsi IUD (Copper T-380A). Pelaksanaan CoC pada Ny. K menunjukkan pentingnya pemantauan berkelanjutan untuk deteksi dini komplikasi, meningkatkan kesiapan ibu, serta mendukung keberhasilan program keluarga berencana pasca persalinan.